Enhanced Electrochemical Oxidation of Hydrogen Peroxide at Hydroxyl Ion-Modified Gold Electrode in Alkaline Media (Journal of Bangladesh Academy of Sciences, 2016)
Chemisorption of hydroxyl ion (OH-) from aqueous solution of KOH at the polycrystalline gold (Au (poly)) electrode under stirring condition was studied. A pre-wave at ca. 0.19 V was observed due to partial discharging of the chemisorbed OH-. The linear plot of the pre-wave current vs. scan rate passed through the origin suggesting that it was associated with a surface confined process. An extraordinary enhanced electrocatalytic oxidation of hydrogen peroxide (HO - 2 ) at the in situ fabricated OH--modified Au (poly) (OH-ôAu (poly)) electrode was achieved. A mechanism of the observed catalytic activity was proposed on the basis of electrostatic attraction between the chemisorbed OH- and partial positively charged hydrogen (Hd+) of HO - 2 molecules.Journal of Bangladesh Academy of Sciences, Vol. 40, No. 2, 125-135, 2016